Facilitating evidence-based and inclusive policy development - Ogutu, Elizabeth; Jalango, Dorcas; Ndetu, Veronica; Nzuki, Esther (2025)
The Turkana County Agriculture Policy 2025 aims at transforming agriculture into a sustainable, market-oriented, and climate-resilient engine of growth. This policy provides a strategic framework to enhance productivity, generate employment, and strengthen rural resilience while promoting sustainable natural resource management. Through the AICCRA project, we played a pivotal role in providing technical backstopping in reviewing the initial draft, supporting the convening of the county steering committee, public participation across four sub-counties, facilitating stakeholder validation workshops, and assisting the county team in finalizing the policy for submission to the County Assembly. This collaboration strengthened the policy development quality, inclusivity, and alignment with both national agricultural transformation strategies and climate-resilient development priorities.